Two new species of Travisiidae (Annelida, Sedentaria) from Thailand - Plathong, Jintana; Plathong, Sakanan; Salazar-Vallejo, Sergio I. (Zootaxa, 2023)
Two new species of Travisiidae, Travisia satunensis sp. nov. and T. thailandensis sp. nov., were collected from different locations in Thailand waters. Travisia satunensis sp. nov. was collected in the Andaman Sea, at 2–14 m water depths. Travisia thailandensis sp. nov. was collected from offshore petroleum concession areas in the Gulf of Thailand, at 50–80 m water depths. Travisia satunensis sp. nov. differs from all other species by having branched annulated branchiae on chaetigers 2–35, each annulated with a single filament, chaetae throughout the body and pygidium with 10 anal cirri, six digitiform and four short cirri, alternately arranged. Travisia thailandensis sp. nov. differs from all other species by having 21 pairs of cirriform, annulated branchiae from chaetiger 2, a mid-ventral groove along body, two last segments achaetous, and nephridiopores on chaetigers 7–14. A key for Travisia species from the Indo-Pacific region is also provided.